The Impact of Green Accounting Practices on Corporate Environmental Performance - Finarsih Septria; Bintang Junita; Slamet Maryoso; Firstianty Wahyuhening Fibriany (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study investigates the impact of green accounting practices on corporate environmental performance, with a focus on manufacturing firms in Indonesia. Green accounting, which involves the identification, measurement, and reporting of environmental costs, is increasingly recognized as a strategic tool for enhancing corporate accountability and sustainability. However, in developing countries, its implementation remains limited and fragmented. Using a qualitative approach, this research explores how green accounting mechanisms are integrated into corporate decision-making processes and how they influence key environmental performance indicators such as energy efficiency and waste reduction. Data were collected through semi structured interviews with environmental and finance managers from five companies actively participating in the PROPER environmental rating program. Thematic analysis revealed that firms with advanced environmental accounting practices achieved higher energy savings and waste reduction outcomes, as well as superior PROPER ratings. These improvements are directly linked to the strategic use of environmental data in operational planning and investment decisions. Nonetheless, challenges such as the lack of technical guidelines, insufficient human resources, and the absence of standardized frameworks remain significant barriers to broader adoption. The study contributes to the growing literature on sustainability accounting in emerging economies and offers practical implications for policymakers and corporate practitioners seeking to institutionalize green accounting as part of sustainable business governance.